Impact of disorder on optical reflectivity contrast of epitaxial Ge2Sb2Te5 thin films. Issue 26 (8th June 2018) - Behrens, Mario; Lotnyk, Andriy; Roß, Ulrich; Griebel, Jan; Schumacher, Philipp; Gerlach, Jürgen W.; Rauschenbach, Bernd
Abstract : Classification of the optical reflectivity contrasts of single-phase, epitaxial Ge2 Sb2 Te5 thin films with respect to the vacancy arrangements. Abstract : The formation of periodically spaced vacancy layers within the metastable phase of Ge–Sb–Te based phase-change materials has recently gained a lot of attention since associated electron delocalization effects induce an insulator–metal transition. In order to fundamentally study the potential of the vacancy ordering phenomena, it is crucial that the highly ordered metastable phase is produced separately from the closely related thermodynamically stable phase. Therefore, in this study, Ge2 Sb2 Te5 thin films with different degrees of structural order are prepared on Si(111) substrates by pulsed laser deposition, putting primary emphasis on achieving high phase purity. Beside metastable cubic Ge2 Sb2 Te5 thin films with disordered cation sublattice and stable trigonal Ge2 Sb2 Te5 thin films, metastable epitaxial films consisting of building blocks with an ABC-type stacking of the Te layers, separated from each other by vacancy layers, are obtained. In these films, no hints on the formation of the trigonal, van-der-Waals bonded Ge2 Sb2 Te5 structure are found, i.e. separation of the highly ordered phases with respect to the stacking of the layers is achieved. The single-phase quality of the Ge2 Sb2 Te5 thin films allowed the classification of the optical reflectivity contrast of different crystalline Ge2 Sb2 Te5 phases with respect to their vacancy ordering. Distinct differences in reflectivity are found, demonstrating the potential of Ge2 Sb2 Te5 to be applied in a novel concept of optical phase-change memory switching between the disordered and ordered Ge2 Sb2 Te5 phase.